Pengembangan Model Pembelajaran Blended Learning Berbantuan Aplikasi Sevima Edlink - Marlina, Emas (LPPM Universitas Advent Indonesia, 2020)
Abstract: The background of the research is emerged by the importance to develop an appropriate learning model in realizing the Ministry of Education and Culture policy in 2020 on Merdeka Belajar-Merdeka. The objective of the research is to adapt and to transform the policy of Merdeka Learning-Merdeka into pratical use by developing a learning models Blended Learning aided by an application of Sevima Edlink in Mathematics classrooms. The research was conducted from April to June 2020. The research method used were literature study and observation. The participants were six students of Mathematics in their 4th semester. The finding showed that after the use of Blended Learning with Sevima Edlink, the average 90,83. Thus, is it cloncluded that Blended Learning using Sevima Edlink is appropriate in Mathematics learning process in order realize Merdeka Belajar-Kampus Merdeka policy. Keyword: Merdeka Belajar-Kampus Merdeka, Blended Learning, Sevima Edlink.